2008
DOI: 10.1029/2008jd010605
|View full text |Cite
|
Sign up to set email alerts
|

Lightning occurrence in relation with elevation, terrain slope, and vegetation cover in the Mediterranean

Abstract: [1] In the frame of this paper, 1-year of lightning data from the experimental network ZEUS operated by National Observatory of Athens is analyzed. The area of interest is the Mediterranean and surrounding countries. At a first stage, the ZEUS data are compared with the data provided by the UK Met Office long-range lightning detection network for the warm period of the year. It was found that although ZEUS system underestimates the nighttime and early morning activity, during the rest of the day ZEUS system de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(87 citation statements)
references
References 24 publications
6
77
2
2
Order By: Relevance
“…Then the lightning location is retrieved (at the central station) using the arrival time difference technique. Further details on the ZEUS network are given in Kotroni and Lagouvardos (2008). Lagouvardos et al (2009) have compared the ZEUS system with the LINET system over a major area of central-western Europe, where the latter system presents its major efficiency and accuracy, and found that the location error of ZEUS was 6.8 km and the detection efficiency 25 %.…”
Section: Zeusmentioning
confidence: 99%
“…Then the lightning location is retrieved (at the central station) using the arrival time difference technique. Further details on the ZEUS network are given in Kotroni and Lagouvardos (2008). Lagouvardos et al (2009) have compared the ZEUS system with the LINET system over a major area of central-western Europe, where the latter system presents its major efficiency and accuracy, and found that the location error of ZEUS was 6.8 km and the detection efficiency 25 %.…”
Section: Zeusmentioning
confidence: 99%
“…Many studies have been conducted in order to correlate the precipitation characteristics and the lightning activity flashes (Soula and Chauzy, 2001;Tapia et al, 1998;Zhou et al, 2002;Kempf and Krider, 2003;Katsanos et al, 2007;Pineda et al, 2010). Tapia et al (1998), analyzed lightning observations from 22 thunderstorms in Florida, concluding that it is possible to derive estimates of precipitation in space and time for heavy rainfall events.…”
Section: A G Koutroulis Et Al: Lightning Activity Rainfall and Flmentioning
confidence: 99%
“…Not all the rain gauges were used for every rainy event, since precipitation measurements were not always readily available due to gaps in the data or rain gauge malfunctioning. Lightning data retrieved from the ZEUS system were provided by the National Observatory of Athens (NOA) in Greece (an assessment of the performance of the ZEUS system has been presented by Morales et al, 2007, and, more recently, by Lagouvardos, 2008, andLagouvardos et al, 2009).…”
Section: Datamentioning
confidence: 99%